Non-lymphomatous malignancies associated with human immunodeficiency virus infected patients (Medical Journal of Indonesia, 2004)
Non-lymphomatous malignancies may also develop in immunocompromised patients. However a detail study about the cases is lacking. Here we describe four cases of solid tumours in HIV seropositive patients. (Med J Indones 2004; 13: 171-2)Keywords:Â solid tumours, HIV infection, radiation therapy, chemotherapy